Pranas Skardžius ir jo kalbotyriniai darbai - Rosinas, Albertas (Baltistica, 1998)
PRANAS SKARDŽIUS AND HIS WORKS IN LINGUISTICS March 26, 1999 marks the centenary of the birth of Pranas Skardžius, a famous Lithuanian linguist, an expert in Lithuanian and Baltic studies, an excellent teacher and research organizer, one of the most distinguished normalizers and fosterers of Standard Lithuanian. The present study reviews Skardžius’ life and his road to science, points out his merits to Lithuanian and Baltic linguistics and looks into his activity and works fostering and improving the Standard Lithuanian language. Skardžius was a versatile and prolific linguist. The list of his works comprises more than 800 items. The majority of his works have entered into the academic heritage of Lithuanian linguistics. His first major study “Die slavischen Lehnwörter im Altlitauischen” (1931) surpasses Alexander Bruckner’s work “Die slavischen Fremdwörter im Litauischen” written as far back as 1877 not only in the volume of data used, but also in a critical approach to the analysis of Slavicisms. In terms of its data and propositions, the study has been and remains relevant to the present day as a handbook to all who investigate Slavicisms or foreign borrowings in general. Lithuanian accentuation was Skardžius’ lifetime interest. The largest work in this field is „Daukša’s Accentuation” (1935). Here the author reveals the archaic elements of accentuation in Daukša’s works, underlines the relevance of Daukša’s stressed texts for further investigation into the history of Lithuanian accentuation. Lithuanian historical accentology, as well as practical accentuation, can gain much from Skardžius’ books “The Accentuation of Standard Lithuanian” (1936) and “The Accentuation of the Lithuanian Language”. The largest and most valuable work written by Skardžius is “The Word Formation of the Lithuanian Language” (1941, 1943) which presents the means of word formation employed by Lithuanian language users to enhance their own word stock. The said study is not only a synchronic description, but also a diachronic investigation which relates Lithuanian word formation and its peculiarities to the peculiarities of the word formation of the Baltic and other Indo-European languages and elucidates the common sources and laws in the word formation of the Indo-European languages. Skardžius’ works on onomastics arc of great value to this day. For example, his study “Lithuanian Hydronyms with -nt-. Their Formation, Origin, Meaning” rejected Raymond Schmittlein’s hypothesis, which claimed that the majority of Lithuanian hydronyms with -nt- were of Germanic origin. Skardžius has had a profound and enduring influence on speech culture. The term bendrinė kalba (the standard language) was created by Skardžius. As far back as the 1930s, he worked out his own criterion system for the codification of Standard Lithuanian (viz. usage, purposefulness and purity) akin to the criteria which emerged in the Prague Linguistic Circle in the 1940s. From 1933 to 1967, he was an active member and editor of „Gimtoji kalba“ (Native Language). In „Gimtoji kalba“, various periodicals and newspapers, as well as in the press of the American Lithuanians, he published more than 500 articles where he skilfully researched the current issues on orthography, phonetics, morphology, syntax, onomastics, terminology, word formation and gave well-grounded recommendations on usage. In the majority of his articles devoted to practical aspects of the language the scholar asserted his view that the codification of a language must be performed by linguists-professionals, but not by dilettantes. Although there has been no full estimation of Skardžius’ contribution to the improvement and development of Standard Lithuanian to date, his impact on speech culture can be firmly qualified as huge. The enormous work performed by Skardžius, a most talented linguist and fosterer of the language, marks a profound and significant stage not only in the development of Lithuanian and Baltic linguistics, but also in Lithuania’s culture; having discovered and contemplated its real value, we will be able to turn to a fresh start.